Safe Haven—Bath House and Library by the Burmese Border - Mizsei Anett (HERITAGE, 2021)
This study gives an overview of contemporary vernacular tendencies in Thai architecture. The research includes ecological, economical, ergonomic and cultural aspects, and the aim is to find a possible future direction for architectural design that is able to incorporate local features and follow traditions yet apply them in a contemporary way. As an example, a case study was carried out about a project realized in Safe Haven Orphanage in Thailand. It consists of two small-scale buildings designed and constructed by TYIN Tegnestue Architects, Sami Rintala and Hans Skotte, together with volunteers and the local community, and they are great examples of a community building “healing architecture”. Due to their aesthetics, their ecological and sustainable approach and their structures, they can provide cultural continuity, which is key for the organic evaluation of regional architecture.